Systems analysis of X-chromosomal miRNAs and their target genes using informatics tools - Mendoza, Ronie B. (Transactions of the National Academy of Science and Technology, 2011)
In an attempt to investigate the potential roles of miRNAs in human intelligence, miRNAs located in the X-chromosome were identified by mining the miRBase database. Out of the 77 miRNAs, 10 were chosen for further analysis based on their differential levels in the various functional parts of the brain: cortex (executive functions, long-term/immediate memory and speech), hippocampus (learning and working memory) and the midbrain (visual and auditory systems, and body movement). Target genes of these ten brain-expressed X-chromosomal miRNAs were predicted and compared with the following randomized miRNAs: ten nonbrain-expressed X-chromosomall miRNAs, ten nonbrain-expressed miRNAs that are not found in the X-chromosome and ten brain-expressed miRNAs that are not found in the X-chromosome. For the brain-expressed X-chromosomal miRNAs, a total of 221 target genes were predicted based on their common targets from three public prediction algorithms: MiRanda, TragetScan and MiRTarget2. These target genes were then annotated and compared according to their gene ontologies (GOs). Chemo-and Bioinformatics analyses indicate that the X-chromosome has potential roles in human intelligence as indicated by the statistically significant GO terms associated with learning, memory and brain development by the target genes of the brain-expressed X-chromosomal miRNAs.